2002
DOI: 10.1152/japplphysiol.01050.2001
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of gluconeogenesis in exercising men by mass isotopomer distribution analysis

Abstract: We evaluated the hypothesis that coordinated adjustments in absolute rates of gluconeogenesis (GNG(ab)) and hepatic glycogenolysis (Gly) would maintain euglycemia and match glucose production (GP) to peripheral utilization during rest and exercise. Specifically, we evaluated the extent to which gradations in exercise power output would affect the contribution of GNG(ab) to GP. For these purposes, we employed mass isotopomer distribution analysis (MIDA) and isotope-dilution techniques on eight postabsorptive (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 52 publications
7
38
1
2
Order By: Relevance
“…We observed a significant decrease of blood glucose concentration during exercise from 5.0 to 4.2 mM after 4 h. A decrease of similar extent has been reported by others, albeit in humans performing exercise at higherintensity levels, up to 65% V O 2 max (15,28,29,44,45). In those studies, subjects were studied 7.5 h after their last meal, and exercise commenced 12 h following completion of their evening meal.…”
Section: H Enrichment In Body Water and At C-5 Of Glucose And Estimatsupporting
confidence: 89%
“…We observed a significant decrease of blood glucose concentration during exercise from 5.0 to 4.2 mM after 4 h. A decrease of similar extent has been reported by others, albeit in humans performing exercise at higherintensity levels, up to 65% V O 2 max (15,28,29,44,45). In those studies, subjects were studied 7.5 h after their last meal, and exercise commenced 12 h following completion of their evening meal.…”
Section: H Enrichment In Body Water and At C-5 Of Glucose And Estimatsupporting
confidence: 89%
“…First, we found that, as predicted by the overexpression studies, muscle GLUT4 levels are reduced in the PGC-1␣ Ϫ/Ϫ mice. Second, it is known that glycogenolysis serves as the chief source of glucose export from liver during exercise (59,60). Whereas hepatic gluconeogenic capacity is reduced in PGC-1␣ Ϫ/Ϫ mice, glycogen stores and glycogenolysis rates are increased (58).…”
Section: Discussionmentioning
confidence: 99%
“…Second, peak exercise does not require a significant contribution of fat metabolism for energy production. As exercise intensity increases, rates of both glycolysis and gluconeogenesis are adjusted to maintain adequate glucose availability (57). Thus, despite the loss of ATGL-mediated intramyocellular lipolysis, peak exercise could remain unaffected.…”
Section: Discussionmentioning
confidence: 99%